(Invited) Surface Composition and Oxygen Exchange Properties of Alkaline Earth-Free Perovskites; LaCo0.6Ni0.4O3. (26th April 2016) - Druce, John; Téllez, Helena; Ishihara, Tatsumi; Kilner, John A.
Abstract : It is well known that alkaline earth additives in conventional perovskite-based solid oxide electrode materials tend to segregate rapidly to the outer surfaces, which is associated with degradation in device performance. It may be possible to avoid these problems by developing materials which do not contain alkaline earth dopants; however, without the oxygen vacancies introduced by alkaline earth doping, the oxygen transport and electro-catalytic properties may suffer. Here, we investigate oxygen transport in the nickel doped lanthanum cobaltite system, and find that the relatively low oxygen diffusivity is dominated by grain boundary transport. Despite this, at higher temperatures, the surface exchange coefficient is comparable to state-of-the-art Sr doped cobaltites. The surface composition of the annealed samples measured by Low Energy Ion Scattering spectroscopy does not appear different from the as-polished samples, suggesting that the surface composition is indeed more stable for this alkaline earth free material.